A new narrow-leaved species of Capparis (Capparaceae) from central Palawan, Philippines - Fici, Silvio (Phytotaxa, 2016)
A new species of Capparis, C. tagbanuorum, is described and illustrated from Palawan Island in the Philippines. It is known from a single locality in Mount Victoria, in forest habitats at medium elevation. The new species is characterized by a peculiar leaf morphology, with blade up to 9 times as long as wide, by the racemose inflorescence and by the size of the petals and the number and length of the stamens. The diagnostic characters are discussed and a key is given for the species of Capparis known from the Philippines.